Modern Mongolia : from khans to commissars to capitalists - Rossabi, Morris (Philip E. Lilienthal book., 2005)
Deprived in Soviet support in 1990, Mongolia turned to international financial agencies for assistance. This book looks at how the country has fared since liberalisation of the economy & finds that fortunes have been mixed. While many Mongolians are better off, the nation as a whole is deteriorating.